Mortality in community-dwelling elderly: coefficient and associated factors - Sarah Caroline Oliveira de Souza Boitrago; Andressa Samantha Oliveira Souza; Pâmela de Oliveira Cunha; Maria Aparecida Vieira; Antônio Prates Caldeira; Jair Almeida Carneiro; Fernanda Marques da Costa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Analyze the coefficient, associated factors, and causes of mortality in community-dwelling elderly. Method: Longitudinal and analytical study. Data collection, at baseline, was performed in the elderly's home. The first wave occurred after 42 months. Complementary data collection identified the cause of death. Variables analyzed: demographic, social, economic, and clinical. Logistic regression was used for data analysis. Results: The coefficient of mortality was 7.9%. The variables associated with mortality were longevity, inability to read, absence of religious practice, stroke, consultation, and hospitalization in the last 12 months. The main groups of primary causes of death were ill-defined and unspecified causes of mortality, respiratory system diseases, and neoplasms. Conclusion: The coefficient of mortality in community-dwelling elderly was lower than national and international studies investigated.